Terminology Commissions in Latvia (1919–1921) and Lithuania (1921–1926): Comparative Research - Kvašīte, Regīna (Acta humanitarica academiae Saulensis, 2025)
The first Terminology Commissions were established in Latvia in 1919, and in Lithuania in 1921. The article discusses the establishment of the Terminology Commissions of Latvia and Lithuania, the organisation of the work and its results based on the research carried out so far, publications in the press and the minutes of the Terminology Commissions meetings. Many similarities were found between the Latvian Terminology Commission and the Lithuanian Terminology Commission, for example, subcommittees of various fields were created to consider terms and the accepted terms were later reviewed by the general commission. However, the main difference is that the Latvian Terminology Commission had more subcommittees and members in them, which allowed to cover a larger number of areas. In both Latvia and Lithuania, lists of terms under consideration were published in the press – mainly in journals Izglītības Ministrijas Mēnešraksts (Monthly of the Ministry of Education) (Latvia) and Švietimo darbas (Work of Education) (Lithuania). The public could also express their opinion. The results of the work of both Terminology Commissions have a lasting value: the dictionaries of Latvian and Lithuanian terms: in Latvia Zinātniskas terminoloģijas vārdnīca (Dictionary of Scientific Terminology) in 1922, in Lithuania Įvardai, arba terminai, priimti Terminologijos komisijos (Terms, Approved by the Terminology Commission) in 1924. However, they differ both in scope and quality of preparation. Specialists from various fields, as well as famous linguists – Latvian Jānis Endzelīns (1873–1961) and Lithuanian Jonas Jablonskis (1860–1930) participated in the work of the Lithuanian and Latvian Terminology Commissions. Although none of them left behind any theoretical works on terminology, their consulting, coining of new or correcting existing terms in their languages was a significant contribution to the development of scientific terminology in their countries. The research shows that the establishment of the first Terminology Commissions and their role in each of the countries should be evaluated similarly, but it is regrettable that due to financial, organisational and personal problems, the activities of Latvian Terminology Commission and Lithuanian Terminology Commission did not last long.